Identifikasi Makrofauna Tanah di Lahan Pertanian Sekitar Wilayah Kawasan Hutan Cagar Alam Mutis Timau - Kristina Dayanti Mbari; Maria M. E. Purnama; Astin E. Mau; Yusratul Aini (Wana Lestari, 2026)
The presence and abundance of soil organisms are influenced by the quality of the vegetation growing above them. Conversely, the activities of soil organisms also affect plant growth and consequently determine the productivity of their habitat. This study aimed to identify soil macrofauna found in agricultural land surrounding the Mutis Timau Nature Reserve forest area. The study was conducted on agricultural land in Fatumnasi Village, Fatumnasi District, South Central Timor Regency. An exploratory approach was employed by directly collecting and observing soil macrofauna in the field. Soil macrofauna samples were collected using the pitfall trap method. The collected specimens were identified using a soil animal ecology identification guide. The results showed that the soil macrofauna consisted of nine orders belonging to the phylum Arthropoda. The arthropods were classified into three classes: Insecta, Malacostraca, and Arachnida. The nine identified orders were Diptera, Coleoptera, Hemiptera, Lepidoptera, Orthoptera, Hymenoptera, Araneae, Isopoda, and Odonata.